Signaling lansdscape of prostate cancer - Lin, X; Aslam, A; Attar, R; Yaylim, I; Qureshi, M Z; Hasnain, S; Qadir, M I; Farooqi, A A (Cellular and Molecular Biology, 2016)
Research over the decades has gradually and sequentially shown that both intratumor heterogeneity and multifocality make prostate cancer difficult to target. Different challenges associated with generation of risk-stratification tools that correlate genomic landscape with clinical outcomes severely influence clinical efficacy of therapeutic strategies. Androgen receptor mediated signaling has gained great appreciation and rewiring of AR induced signaling cascade in absence of androgen, structural variants of AR have provided near complete resolution of genomic landscape and underlying mechanisms of prostate cancer. In this review we have attempted to provide an overview of most recent advancements in our knowledge related to different signaling cascades including TGF, SHH, Notch, JAK-STAT in prostate cancer progression and development.